MOLECULAR-GENETIC FACTORS, ASSOCIATED WITH AORTIC STENOSIS DEVELOPMENT - T. A. Tipteva; O. S. Chumakova; D. A. Zateyshchikov (Российский кардиологический журнал)
Aortic stenosis (AS) is one of the most prevalent valvular heart disorders in patients older than 65 years. Regardless the studied molecular mechanisms of development and progression of the disease, surgical treatment is recently the only successful method of help. Due to lots of comorbidities of older patients, there are obstacles to recommend surgical valve replacement, even knowing an adverse prognosis of conservative treatment. Search for new approaches to earlier assessment of adverse risk factors, speed of progression of this disease, would help to evaluate the necessity of earlier treatment and could make to slow down the progression of the disease. One of directions for this — is a search for genetic markers. This review focuses on the main known molecular mechanisms and genetic markers related to them, that are associated with AS.